Highly Compression‐Tolerant Supercapacitor Based on Polypyrrole‐mediated Graphene Foam Electrodes. (18th October 2012) - Zhao, Yang; Liu, Jia; Hu, Yue; Cheng, Huhu; Hu, Chuangang; Jiang, Changcheng; Jiang, Lan; Cao, Anyuan; Qu, Liangti
<x xml:space="preserve">Abstract</x> Deformation‐tolerant devices are vital for the development of high‐tech electronics of unconventional forms. In this study, a highly compressible supercapacitor has been fabricated by using newly developed polypyrrole‐mediated graphene foam as electrode. The assembled supercapacitor performs based on the unique and robust foam electrodes achieves superb compression tolerance without significant variation of capacitances under long‐term compressive loading and unloading processes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>